The Influence of the Quizizz-Assisted Problem Based Learning (PBL) Model on the Mathematical Literacy Ability of Grade V Students of SD Negeri 92 Kendari - Anidi Anidi; Nurhaeda Nurhaeda; Sri Jumiati Permatasari (EDUKASIA Jurnal Pendidikan dan Pembelajaran, 2025)
The purpose of this study is to determine the influence of the Problem-Based Learning (PBL) model fostered by Quizizz on the mathematical literacy ability of fifth-grade students of SD Negeri 92 Kendari. Quantitative approach with quasi-experimental design using Non-equivalent Control Group Design. The sample in this study consisted of two classes: VB as an experimental group, which received learning through a PBL model integrated with Quizizz, and VC as a control group, which was taught using conventional methods. Data was collected using mathematical literacy tests in the form of pretests and posttests, supported by student response questionnaires and class activity observation sheets. Data analysis using SPSS Windows 27, including normality test, homogeneity test, paired sample ttest, and independent sample t-test. The results showed a significant improvement in students' mathematical literacy skills in the experimental group compared to the control group. This is evidenced by an independent sample t-test that yields a significance value of 0.028 (<0.05), indicating that the null hypothesis is rejected while the alternative hypothesis is accepted. The results of the observations showed that students in the experimental group showed higher engagement, better problem-solving skills, and higher confidence in conveying ideas. The results of this study confirm that PBL with Quizizz is effective in improving mathematical literacy.